2021
DOI: 10.1007/s00216-021-03455-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on the use of elemental profiles to authenticate aromatic rice: the case of Basmati and Thai rice

Abstract: Among the thousands of existing rice varieties, aromatic rice has increasingly attracted consumer’s preference in recent years. Within aromatic rice, Basmati, cultivated in some regions in Pakistan and India, is highly demanded. Other aromatic rice, cultivated in specific regions, for instance in Thailand (commonly referred to as Jasmine Thai rice), are also highly appreciated by consumers. In this work, the elemental profiles of commercially available rice samples (17 Basmati, 11 Thai, and 7 Long Grain rice) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Because of its unique aroma and excellent grain quality, fragrant rice is loved by consumers worldwide. Compared with nonfragrant rice, farmers can earn higher profits by planting fragrant rice [ 7 ]. Hundreds of compounds can contribute to the unique flavor of fragrant rice.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its unique aroma and excellent grain quality, fragrant rice is loved by consumers worldwide. Compared with nonfragrant rice, farmers can earn higher profits by planting fragrant rice [ 7 ]. Hundreds of compounds can contribute to the unique flavor of fragrant rice.…”
Section: Introductionmentioning
confidence: 99%
“…Fragrant rice is famous for its special aroma in the world (Dumitrascu et al, 2021;Moogi et al, 2021), and 2-acetyl-1pyrroline (2-AP) has been identified as the key and main component of that aroma in recent years (Jezussek et al, 2002;Mahattanatawee and Rouseff, 2014;Poonlaphdecha et al, 2016). Over the past two decades, scientists have made attempts to understand the biosynthetic mechanism of 2-AP.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers have focused on the applications of stable isotopes for the determination of the geographical origin of various plant and food products, such as tea ( Zhou et al, 2019 ), green tea ( Ni et al, 2018 ), milk ( Dong, Xiao, & Luo, 2017 ), and wheat ( Luo et al, 2015 ). To date, various techniques have been reported for the determination of geographical origin of rice in several countries such as inductively coupled plasma optical emission spectrometry ( Chung et al, 2015 , Gonzálvez et al, 2011 , Li et al, 2012 ), inductively coupled plasma mass spectrometry (ICP-MS) ( Du et al, 2018 , Kokot and Phuong, 1999 , Kongsri et al, 2021 , Li et al, 2012 , Shen et al, 2013 ), high resolution inductively coupled plasma mass spectrometry (HR-ICP-MS) ( Ariyama et al, 2012 , Cheajesadagul et al, 2013 ), energy-dispersive X-ray Fluorescence spectroscopy ( Dumitrascu, Fiamegos, & de la Calle Guntiñas, 2021 ), isotope ratio mass spectrometry (IRMS) ( Chung et al, 2016 , Korenaga et al, 2010 , Suzuki et al, 2008 , Wang et al, 2020 ), and instrumental neutron activation analysis (INAA) ( Kato, De Nadai Fernandes, Bacchi, & Sarriés, 2018 ; Kukusamude & Kongsri, 2018; Salim, Mostapa, Othman, Daud, Harun, & Mohamed, 2020 ).…”
Section: Introductionmentioning
confidence: 99%